2022
DOI: 10.3390/cimb44100336
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Radium-223 on the Gut Microbiota of Prostate Cancer Patients: A Pilot Case Series Study

Abstract: Radium-223 (Ra-223) is a targeted nuclear medicine therapy for castration-resistant prostate cancer with bone metastases. Its major route of elimination is the intestine. There is overwhelming evidence that the gut microbiota is altered by ionizing radiation (IR) from radiotherapy treatments. Nevertheless, it is known that extrapolation of outcomes from radiotherapy to nuclear medicine is not straightforward. The purpose of this study was to prospectively determine the effect of Ra-223 on selected important ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Indeed, increased abundance of Proteobacteria has been previously identified as a potential indicator of inflammation and disease [51] . In contrast, Lactobacillus, Clostridium leptum, and Clostridium coccoides were decreased in PCa patients [48] . Lactobacillus has been shown to have anti-cancer effects in colorectal cancer, and both Clostridium species contribute to SCFA production [52] , [53] , [54] .…”
Section: The Gut Microbiome and Cancer In The Bonementioning
confidence: 78%
See 2 more Smart Citations
“…Indeed, increased abundance of Proteobacteria has been previously identified as a potential indicator of inflammation and disease [51] . In contrast, Lactobacillus, Clostridium leptum, and Clostridium coccoides were decreased in PCa patients [48] . Lactobacillus has been shown to have anti-cancer effects in colorectal cancer, and both Clostridium species contribute to SCFA production [52] , [53] , [54] .…”
Section: The Gut Microbiome and Cancer In The Bonementioning
confidence: 78%
“…Moreover, Lactobacillus animalis supplementation in patients with osteonecrosis of the femoral head has been found to have protective effects on the bone microenvironment, inducing angiogenesis and bone growth [55] . After receiving Ra-223, levels of Bacteroidetes, Prevotella, Lactobacillus, Bidifidobacterium, Clostridium coccoides, and Bacteroides fragilis were all decreased [48] . Taken together, this data suggests that bone metastatic PCa patients have altered gut microbial signatures, and these signatures are further altered by Ra-223 treatment.…”
Section: The Gut Microbiome and Cancer In The Bonementioning
confidence: 95%
See 1 more Smart Citation
“…Radiotherapy results in dysregulation of the gut microbiota, which negatively affects the diversity and richness of gut bacterial diversity, potentially causing an enrichment of harmful microbiota ( Proteobacteria and Fusobacteria ) and a decrease in beneficial microbiota ( Faecalibacterium and Bifidobacterium ) [ 47 , 48 ]. El Alam et al discovered a significant alteration in the gut microbiome composition during pelvic chemotherapy and radiotherapy (CRT), with increases in Proteobacteria and decreases in Clostridiales , whereas after CRT, the gut microbiome composition changed, with increases in Bacteroides species [ 49 ].…”
Section: Cancer Treatment Efficacy and Toxicity Are Influenced By Gut...mentioning
confidence: 99%
“…The relationship between GM dysbiosis and several diseases has been established; some examples include periodontal disease, cancer, obesity, diabetes, and chronic fatigue syndrome ( Ditto et al., 2021 ). However, a growing number of studies have shown that differences between healthy and bio-imbalanced microbiota may be associated with prostate diseases, such as chronic prostatitis, BPH, prostate cancer, and other prostate diseases ( Fernandes et al., 2022 ). Tsai et al.…”
Section: Introductionmentioning
confidence: 99%